Challenges of Digital Learning in English Reading Classrooms: A Qualitative Study of Students with Diverse Learning Styles - Zul Astri; Nuraeni Nuraeni; Isnaeni Wahab; Sitti Aisyah (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
The integration of digital learning tools has transformed teaching and learning practices, particularly in English reading classrooms. While digital learning offers flexibility and access to diverse multimedia resources, its effectiveness is influenced by students’ varied learning styles. This study aims to examine the challenges experienced by visual, auditory, and kinesthetic learners in digital English reading environments. A qualitative case study design was employed. Data were collected from 64 undergraduate students using the Barsch Learning Style Inventory, from which 15 participants representing different learning styles were purposively selected for in-depth interviews. The participants were drawn from a private university and had prior experience with both face-to-face and digital learning contexts. The findings reveal several key challenges, including internet connectivity issues, screen-related discomfort, device limitations, limited interactivity, and digital distractions. These challenges affect learners differently: visual learners struggle with limited visual interaction, auditory learners are affected by disrupted audio input, and kinesthetic learners face difficulties engaging in less interactive environments. The study highlights that digital learning challenges are not experienced uniformly but are shaped by learners’ preferences. It underscores the need for more inclusive and multimodal digital learning designs to enhance student engagement and learning outcomes.